Pengaruh Penggunaan Media Pembelajaran Makromedia Flash 8 Terhadap Hasil Belajar Geografi Peserta Didik di Kelas Xi IPS SMAN 2 Lubuk Basung - Siska Janelia Putri; Nefilinda Nefilinda; Ade Irma Suryani (STKIP PGRI Sumatera Barat, 2022)
This study aims to determine how the influence of the use of Macromedia Flash 8 learning media on the learning outcomes of students' geography in class XI IPS SMA N 2 Lubuk Basung.The type of research used in this research is a quasi-experimental type of research. The subjects in this study were students of class XI IPS 1, XI IPS 2, XI IPS 3 and Class XI IPS 4 who took geography lessons at SMA N 2 Lubuk Basung in the academic year 2021/2022, with a total of 121 students.The results of the study found that: This study aims to determine the effect of the application of macromedia flash 8-based learning media on geography subjects in class XI IPS SMA N 2 Lubuk Basung. To determine whether there is an influence of the applied learning media, the researchers conducted a t-test to obtain the results of the hypothesis from student learning outcomes. Based on the data that has been processed, the results of the t-test are obtained with a significant value of 0.000 <0.05, meaning that Ha is accepted and H0 is rejected, so that the data can be concluded that there is an effect of using macromedia flash 8 learning media on the geography learning outcomes of students in class XI social studies. SMAN 2 Lubuk Basung.